Kyrgyz Republic - Poverty Mapping : Methodology and Key Findings - Mahadevan, Meera; Yoshida, Nobuo; Praslova, Larisa (World Bank, Washington, DC, 2014)
This report poverty mapping for Kyrgyz describes the process of and results from a poverty mapping exercise for the Kyrgyz Republic, using the Kyrgyz Integrated Household Survey (KIHS 2009) and the Population and Housing Census (2009). Poverty mapping is an exercise to estimate poverty incidence at a level where a typical household income and expenditure survey cannot produce statistically reliable poverty estimates due to high sampling errors. In the Kyrgyz Republic, official poverty rates are not produced below oblast level, as the sampling errors of the survey data become non negligible. Various poverty mapping methodologies were devised to overcome increasing imprecision of poverty estimates as they are disaggregated. The goal for the poverty maps of the Kyrgyz Republic was to obtain poverty estimates at rayon or district level, a level at which the survey is not representative. For the purposes of this poverty map, all 7 oblasts of the Kyrgyz Republic have been considered and one out of the two cities holding a similar status to oblasts.